Alimentação saudável como forma de qualidade de vida - Ferreira, Felipe Vermeulen [UNESP]; Campos, Sérgio [UNESP]; Leal, Isabel Susana dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Healthy eating is very important for a longer and better life. Who cares about the health is like forgetting to perfect the choices of food. Currently we experience a great dietary transition where left to consume natural foods to be bombarded from processed foods with preservatives, flavorings, pesticide and etc. However, they are minorities in the population of the table, which increases the risk of disease because healthy eating is not just salad with grilled chicken breast, but a delicious mix of food. So you need to make a change in eating behavior, ie a nutritional education. The project aims at preparing the physical space and attention of children, a proposal to integrate and raise awareness on school work, expanding health and improving quality of life and food, as well as provide opportunities for students of Agronomy in the application of technical knowledge adapted in the use of pesticides and chemical fertilizers, the public served and expand their technical knowledge acquired during the course. The Extension Project is developed with support of the City, Departments of FCA, Supervision Farms FCA and House Agriculture Botucatu / SAAESP. The maintenance and expansion of areas with greenery comes involving undergraduates, teachers of the FCA and the Municipal School, with emphasis on improving the quality of life areas and food safety of students. Students of FCA come constantly reshaping the physical space to suit the needs raised in the garden, orchard, garden and medicinal plants, always looking to take nutritional knowledge and use of medicinal plants, given by qualified professionals. The daily production of vegetables, vegetables, herbs and spices, partly meet the needs of school meals provided by the Botucatu Municipality, as well as garden maintenance has contributed to the school beautification. The project has enabled the training of several students with extension bag and volunteers, ie over 5 years over 50 students have gone through this training, and produced an average of 800 kg of vegetable crops per year.

A alimentação saudável é muito importante para uma vida mais longa e melhor. Quem se preocupa com a saúde não tem como se esquecer de caprichar nas escolhas dos alimentos. Atualmente vivenciamos uma grande transição alimentar, onde se deixou de consumir alimentos naturais para sermos bombardeados de alimentos industrializados, com conservantes, aromatizantes, agrotóxico e etc. Porém, são minorias na mesa da população, o que aumenta o risco de contrair doenças, pois uma alimentação saudável não é só salada com peito de frango grelhado e sim uma combinação deliciosa de alimentos. Assim, é preciso fazer uma mudança de comportamento alimentar, ou seja, uma reeducação alimentar. O projeto visa à adequação do espaço físico e atenção das crianças, como proposta de integrar e sensibilizar no trabalho escolar, ampliando as condições de saúde e melhorando a qualidade de vida e alimentar, bem como oferecer oportunidades aos alunos da Agronomia na aplicação dos conhecimentos técnicos adaptados no uso de agrotóxicos e fertilizantes químicos, ao público atendido e ampliar seus conhecimentos técnicos adquiridos durante o curso. O Projeto de Extensão é desenvolvido com apoio da Prefeitura Municipal, Departamentos da FCA, Supervisão das Fazendas da FCA e Casa da Agricultura de Botucatu/SAAESP. A manutenção e ampliação das áreas com hortaliças vem envolvendo alunos de graduação, docentes da FCA e da Escola Municipal, destacando-se a melhoria da qualidade de vida, das áreas e segurança alimentar dos alunos. Os alunos da FCA vêm reformulando constantemente o espaço físico para adequação das necessidades levantadas na horta, pomar, jardim e plantas medicinais, sempre procurando levar conhecimentos nutricionais e uso de plantas medicinais, indicadas por profissionais habilitados. As produções diárias de verduras, legumes, plantas medicinais e condimentos, atendem parcialmente as necessidades da merenda escolar fornecida pela Prefeitura Municipal de Botucatu, bem como a manutenção do jardim vem contribuindo para o embelezamento da escola. O projeto tem possibilitado o treinamento de diversos estudantes com bolsa de extensão e de voluntários, ou seja, ao longo de 5 anos mais de 50 alunos passaram por esse treinamento, sendo produzida uma média de 800 kg de olerícolas por ano.
Keywords: Extension; Vegetables; Project; Extensão; Hortaliças; Projeto